Perlindungan Hukum bagi Konsumen terhadap Peredaran Obat Sirup Anak yang Menyebabkan Terjadinya Gagal Ginjal Akut: Studi Kasus pada BPOM Kota Kupang - Carla Nggeolima; Siti Ramlah Usman; Yossie M.Y. Jacob (Majelis: Jurnal Hukum Indonesia, 2024)
This study aims to find out and analyze the legal protection for consumers against the circulation of children's syrup drugs that cause acute kidney failure in BPOM Kupang City. This study is an empirical legal research that is analyzed in a qualitative descriptive manner using primary data and secondary data obtained from interviews and literature studies. The results of this study show (1) legal protection for consumers over the circulation of children's syrup drugs, which causes acute kidney failure which is known that consumer protection in Indonesia currently according to researchers is still not running well. (2) the responsibility of the Food and Drug Supervisory Agency in providing protection for children's syrup drugs that cause acute kidney failure which is known to indicate that BPOM's task of supervising drugs is not effective because there are still many cases of dangerous circulation of children's syrup drugs.